Kala II At long Labor Presentation Breech Babies Apgar And Value First Minute - Wagiyo Wagiyo; Desak Parwati; Kurniati Puji Lestari (Poltekkes Kemenkes Semarang, 2012)
The purpose of this study was to determine the relationship long second stage of labor in breech presentation of the baby-minute Apgar I. This type of research is the analytic study with a retrospective approach, the study population in this study were all mothers who gave birth by vaginal delivery breech presentation. The sample size was 160 people. The results obtained have strong relationships and patterns between the old perfect negative second stage of labor in breech presentation with a first-minute Apgar value with the value r = -0.704, meaning that the longer second stage of labor with breech presentation the lower the value of the first minute Apgar babies and value determination coefficient of 0.770. which means, the first minute Apgar babies or equation that was obtained either to explain the variable value of the first minute Apgar babies born by vaginal breech presentation.